2022
DOI: 10.1001/jamanetworkopen.2022.17251
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Repeated Exposure to Hurricanes and Mental Health in a Representative Sample of Florida Residents

Abstract: This survey study examines the association between repeated hurricane exposure and mental health and functional impairment outcomes among Florida residents exposed to hurricanes Irma and Michael.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 56 publications
4
28
0
Order By: Relevance
“…Our finding might imply “spillover” effects from Hurricane Ida (e.g., via media exposure) or continued mental health concerns from the concurrent COVID‐19 pandemic. One study showed that media‐based exposure to hurricanes in Florida residents repeatedly exposed to Hurricanes Irma and Michael were associated with ongoing psychological distress (Garfin et al., 2022 ). Another panel survey study in Florida determined that exposure to storm‐related media accounts of the impending storm were associated with adverse psychological distress post‐Irma (Thompson et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding might imply “spillover” effects from Hurricane Ida (e.g., via media exposure) or continued mental health concerns from the concurrent COVID‐19 pandemic. One study showed that media‐based exposure to hurricanes in Florida residents repeatedly exposed to Hurricanes Irma and Michael were associated with ongoing psychological distress (Garfin et al., 2022 ). Another panel survey study in Florida determined that exposure to storm‐related media accounts of the impending storm were associated with adverse psychological distress post‐Irma (Thompson et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding might imply "spillover" effects from Hurricane Ida (e.g., via media exposure) or continued mental health concerns from the concurrent COVID-19 pandemic. One study showed that media-based exposure to hurricanes in Florida residents repeatedly exposed to Hurricanes Irma and Michael were associated with ongoing psychological distress (Garfin et al, 2022). Another panel survey study in Florida determined that exposure to storm-related media accounts of the impending storm were associated with adverse psychological distress post-Irma (Thompson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the 2017 measure provides a more direct comparison with media exposure to COVID‐19, as participants were also directly exposed to that hazard in real time. Although Hurricane Michael was also a catastrophic hurricane, it made landfall in Florida in an area of the state with relatively low population density; thus, most of our sample was exposed to Hurricane Michael and other 2018 hurricanes via the media or indirectly (e.g., knowing someone exposed) (Garfin et al., 2022 ). See Supporting Information for exact items from the survey and full results using the 2018 media exposure data.…”
Section: Methodsmentioning
confidence: 99%